2012
DOI: 10.3818/jrp.14.2.2012.79
|View full text |Cite
|
Sign up to set email alerts
|

Examining Metal Theft in Context: An Opportunity Theory Approach

Abstract: Although law enforcement agencies, policymakers, and communities have had to confront the issue of increasing metal theft for the past several years, almost no academic literature has attempted to examine the correlates of metal theft and subsequent policy implications. This exploratory study profiles the theft of metal from commercial and residential dwellings through analysis of recorded crime data from April 2008 through July 2010 in Rochester, New York. An opportunity framework guided the analyses. Spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…This finding is consistent with the results reported by Posick et al (2012) who found that the number of items stolen during burglaries in Rochester, NY, was not significantly associated with whether metals were stolen, which they interpreted as suggesting that houses were being specifically targeted for their metals as opposed to metals being stolen simply as bycatch of other items taken. We also found no support for the hypothesis that changes in ''live'' copper cable thefts are associated with the rate of unemployment in the United Kingdom.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is consistent with the results reported by Posick et al (2012) who found that the number of items stolen during burglaries in Rochester, NY, was not significantly associated with whether metals were stolen, which they interpreted as suggesting that houses were being specifically targeted for their metals as opposed to metals being stolen simply as bycatch of other items taken. We also found no support for the hypothesis that changes in ''live'' copper cable thefts are associated with the rate of unemployment in the United Kingdom.…”
Section: Discussionsupporting
confidence: 83%
“…In this research note, we provide further evidence for the metal price-theft hypothesis (Posick et al 2012;Sidebottom et al 2011): Positive movements in the average monthly price of copper are shown to be significantly associated with increases in the monthly count of ''live'' copper cable theft. We provide support for this hypothesis using data for a period in which abrupt changes in the price of copper were not only observed but were accompanied by abrupt (almost identical) changes in the theft of copper cabling, as predicted.…”
Section: Discussionmentioning
confidence: 84%
“…As an emerging crime problem, the study of metal theft is only at the start of this spectrum, with most studies focusing on regional variation. Indeed, there have so far been few studies of metal theft of any type: the present authors were able to find only four empirical articles (Whiteacre and Howes, 2009;Sidebottom et al, 2011;Posick et al, 2012;Sidebottom et al, 2014) on the subject, together with a small number of reports from government and other organisations.…”
Section: Introductionmentioning
confidence: 79%
“…The only published study of which the present authors are aware that considered intraregional variation of metal theft is Posick et al (2012). They found that commercial and residential burglaries in Rochester, NY, in which metal was stolen were clustered in certain areas of the city, but were less clustered than burglaries in which metal was not stolen.…”
Section: Introductionmentioning
confidence: 91%
“…(6) House prices (HSEPRICE) were obtained from the ONS at the geography of analysis areas; and (7) the presence of payday lending shops, mortgage brokers, and pawnbrokers (LENDERS) was determined using actual locations of these facilities. LENDERS quantifies the potential for criminogenesis because such facilities create adequate grounds for burglary [46][47][48]. The variable, LENDERS was constructed by searching the yellow pages and querying unique locations of operational facilities using the Google mapping application.…”
Section: Data and Variablesmentioning
confidence: 99%